Flowers of mold : stories - Ha, Sŏng-nan, 1967- (Korean literature series., 2019)
A woman meets her next-door neighbor and loans her a spatula, then starts suffering horrific gaps in her memory. A man, feeling jilted by an unrequited love, becomes obsessed with sorting through his neighbors' garbage in the belief that it will teach him how to better relate to people. A landlord decides to raise the rent, and his tenants hatch a plan to kill him at a team-building retreat.